The Moderating Effects of Financial Inclusion on Qardhul Hassan Financing Acceptance in Nigeria: A Proposed Framework - Zauro, Nurudeen Abubakar; Saad, Ram Al Jaffri; Sawandi, Norfaiezah (International Journal of Economics and Financial Issues, 2016)
This paper, which is conceptual in nature, discusses the moderating effects of the relationship between several factors that may affect the acceptance of Qardhul Hassan financing in Nigeria. The proposed variables under examination are attitude towards Qardhul Hassan financing, knowledge of Qardhul Hassan financing, perceived benefits, perceived government support and religious obligations while financial inclusion serves as a moderator variable. If validated, the work would be used as a proposed financing model to the government, policy makers, regulators, practitioners and other stakeholder’s vis-Ã -vis curbing the adverse effects of financial exclusion in various jurisdictions of the emerging markets. Keywords: Qardhul Hassan, Financial Inclusion, Islamic Finance JEL Classifications: D14, G21